Risk stratification in hf with mid-range LVEF: the role of cardiopulmonary exercise testing. (25th November 2020) - Rocha, B.M.L; Lopes Da Cunha, G.J; Lopes, P.M.D; Freitas, P.N; Gama, F; Brizido, C; Strong, C; Andrade, M.J; Ventosa, A; Tralhao, A; Aguiar, C.M.T; Durazzo, A; et al.
Abstract: Background: Cardiopulmonary exercise testing (CPET) is recommended in the evaluation of selected patients with Heart Failure (HF). Notwithstanding, its prognostic significance has mainly been ascertained in those with left ventricular ejection fraction (LVEF) <40% (i.e., HFrEF). The main goal of our study was to assess the role of CPET in risk stratification of HF with mid-range (40–49%) LVEF (i.e., HFmrEF) compared to HFrEF. Methods: We conducted a single-center retrospective study of consecutive patients with HF and LVEF <50% who underwent CPET from 2003–2018. The primary composite endpoint of death, heart transplant or HF hospitalization was assessed. Results: Overall, 404 HF patients (mean age 57±11 years, 78.2% male, 55.4% ischemic HF) were included, of whom 321 (79.5%) had HFrEF and 83 (20.5%) HFmrEF. Compared to the former, those with HFmrEF had a significantly higher mean peak oxygen uptake (pVO2) (20.2±6.1 vs 16.1±5.0 mL/kg/min; p<0.001), lower median minute ventilation/carbon dioxide production (VE/VCO2) [35.0 (IQR: 29.1–41.2) vs 39.0 (IQR: 32.0–47.0); p=0.002) and fewer patients with exercise oscillatory ventilation (EOV) (22.0 vs 46.3%; p<0.001). Over a median follow-up of 28.7 (IQR: 13.0–92.3) months, 117 (28.9%) patients died, 53 (13.1%) underwent heart transplantation, and 134 (33.2%) had at least one HF hospitalization. In both HFmrEF and HFrEF, pVO2 <12 mL/kg/min, VE/VCO2 >35 and EOV identified patients at higher risk for events (all p<0.05). In Cox regression multivariate analysis, pVO2 was predictive of the primary endpoint in both HFmrEF and HFrEF (HR per +1 mL/kg/min: 0.81; CI: 0.72–0.92; p=0.001; and HR per +1 mL/kg/min: 0.92; CI: 0.87–0.97; p=0.004), as was EOV (HR: 4.79; CI: 1.41–16.39; p=0.012; and HR: 2.15; CI: 1.51–3.07; p<0.001). VE/VCO2, on the other hand, was predictive of events in HFrEF but not in HFmrEF (HR per unit: 1.03; CI: 1.02–1.05; p<0.001; and HR per unit: 0.99; CI: 0.95–1.03; p=0.512, respectively). ROC curve analysis demonstrated that a pVO2 >16.7 and >15.8 mL/kg/min more accurately identified patients at lower risk for the primary endpoint (NPV: 91.2 and 60.5% for HFmrEF and HFrEF, respectively; both p<0.001). Conclusions: CPET is a useful tool in HFmrEF. Both pVO2 and EOV independently predicted the primary endpoint in HFmrEF and HFrEF, contrasting with VE/VCO2, which remained predictive only in latter group. Our findings strengthen the prognostic role of CPET in HF with either reduced or mid-range LVEF. Funding Acknowledgement: Type of funding source: None